The role of a key transcription factor PU.1 in autoimmune diseases - Fang, Yilong; Chen, Weile; Li, Zhe; Chen, Yu; Wu, Xuming; Zhu, Xiangling; Wang, Huihui; Chen, Xiaochun; Liang, Qiuni; Huang, Jinghua; Han, Xintong; Hong, Wenming; et al. (Frontiers in Immunology, 2022)
PU.1, a transcription factor member of the E26 transformation-specific family, affects the function of a variety of immune cells in several physiological and pathological conditions. Previous studies studying the role of PU.1 in pathological conditions have mainly focused on immune system-related cancers, and a series of articles have confirmed that PU.1 mutation can induce a variety of immune cell-related malignancies. The underlying mechanism has also been extensively validated. However, the role of PU.1 in other major immune system-related diseases, namely, systemic autoimmune diseases, is still unclear. It was only in recent years that researchers began to gradually realize that PU.1 also played an important role in a variety of autoimmune diseases, such as rheumatoid arthritis (RA), experimental autoimmune encephalomyelitis (EAE) and systemic lupus erythematosus (SLE). This review article summarizes the findings of recent studies that investigated the role of PU.1 in various autoimmune diseases and the related underlying mechanisms. Furthermore, it presents new ideas and provides insight into the role of PU.1 as a potential treatment target for autoimmune diseases and highlights existing research problems and future research directions in related fields.